Internal Control System for the Management of Petty Cash Funds at the UPT Office of Labor Supervision Region I, North Sumatra Province - Hikmatul Fadilah; Rahmat Daim Harahap (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This writing is entitled "Internal Control System for the Management of Petty Cash Funds at the UPT Office of Labor Supervision Region I of North Sumatra Province" against the background that the development of the company is strongly influenced by the smooth running of the company in managing cash in and cash out. The most liquid asset in a company is cash. Which has the aim of seeing the company implement an internal control system so that the petty cash fund management procedures in the company can function properly. This type of research data uses active and passive primary data, namely data obtained from field surveys or the results of observations and interviews. moreover primary data, researchers also use internal and external secondary data. The conclusion of this paper is that the petty cash fund management procedure at the UPT Office of Labor Supervision Region I of North Sumatra Province is quite good and the internal control of each procedure has been carried out even though there are still some that are not in accordance with the theoretical basis.